A very rare clinical case of the inversion of all internal body organs: a complex case of laparoscopic gastrectomy in an obese woman - Muataz Aaasi; Aya Alkasti; Marwan Al-Raeei; Muhammad Ghanem; Bisan Ahmad; Chadi Azmeh (Journal of Rare Diseases)
Abstract Situs inversus totalis (SIT) is a rare congenital condition characterized by the complete inversion of thoracic and abdominal organs, posing significant challenges in clinical diagnosis and surgical procedures. This case report details the management of a 42-year-old female patient with morbid obesity (BMI of 43.75 kg/m2) who was incidentally diagnosed with SIT during her preoperative assessment for laparoscopic sleeve gastrectomy (LSG). Despite her previous unsuccessful attempts at weight loss through lifestyle modifications, the patient underwent a thorough multidisciplinary evaluation, including input from specialists across various fields, to ensure her safety and optimize surgical outcomes. Preoperative imaging confirmed the mirror-image arrangement of her internal organs, which necessitated careful surgical planning. The laparoscopic procedure was successfully completed without complications, and the patient experienced significant weight loss postoperatively, ultimately weighing 81 kg at her follow-up visit. This report emphasizes the importance of understanding the anatomical nuances of situs inversus in surgical contexts, advocating for tailored techniques in such atypical cases. As obesity and related surgical interventions become increasingly common, the insights gained from this case aim to enhance clinical management practices for similar patients.